European Society of Gynaecological Oncology Guidelines for the Management of Patients With Vulvar Cancer. Issue 4 (1st May 2017) - Oonk, Maaike H.M.; Planchamp, François; Baldwin, Peter; Bidzinski, Mariusz; Brännström, Mats; Landoni, Fabio; Mahner, Sven; Mahantshetty, Umesh; Mirza, Mansoor; Petersen, Cordula; Querleu, Denis; Regauer, Sigrid; et al.
Abstract : Objective: The aim of this study was to develop clinically relevant and evidence-based guidelines as part of European Society of Gynaecological Oncology's mission to improve the quality of care for women with gynecologic cancers across Europe. Methods: The European Society of Gynaecological Oncology Council nominated an international development group made of practicing clinicians who provide care to patients with vulvar cancer and have demonstrated leadership and interest in the management of patients with vulvar cancer (18 experts across Europe). To ensure that the statements are evidence based, the current literature identified from a systematic search has been reviewed and critically appraised. In the absence of any clear scientific evidence, judgment was based on the professional experience and consensus of the development group ( expert agreement ). The guidelines are thus based on the best available evidence and expert agreement. Prior to publication, the guidelines were reviewed by 181 international reviewers including patient representatives independent from the development group. Results: The guidelines cover diagnosis and referral, preoperative investigations, surgical management (local treatment, groin treatment including sentinel lymph node procedure, reconstructive surgery), radiation therapy, chemoradiation, systemic treatment, treatment of recurrent disease (vulvar recurrence, groin recurrence, distant metastases), and follow-up.